16p11.2 Microduplication and associated symptoms: A case study. Issue 4 (2nd October 2018) - Knoll, Martin; Arnett, Kirsten; Hertza, Jeremy
ABSTRACT: The minimal amount known regarding chromosomal microduplications and microdeletions presents a fascinating new direction of research into better understanding misunderstood symptoms and overall genomic influence. Specifically, the 16p11.2 microduplication has been associated with a myriad of possible cognitive, physical, and emotional symptoms. The purpose of this study is to inform the reader of the biological basis of the 16p11.2 microduplication, review sources that suggest a link between the microduplication and clinically relevant diagnoses/sources of impairment, and to better understand the implications and development of symptoms through the illustration of a case example. The case study involves an adolescent African-American female that possesses the 16p11.2 microduplication and focuses on the patient's intellectual and developmental delays, seen through self-report and analysis of her neurocognitive assessment results. Additionally, the patient's associated health complications, such as the development of seizures and a possibly compromised immune system, along with the development of anxiety and depression, are discussed. Implications toward the need for more robust protocol in testing and tracking the effects of this microduplication, such as implementing immunosorbent assay testing at the first sign of associated symptoms, are explored. Limitations are discussed.